The effectiveness of driving school committee at the primary school level - Redjeki, Endang Sri; Gonadi, Leni (Edelweiss Applied Science and Technology, 2025)
While existing research on school committees has emphasized capacity-building and evaluative measures, their role in policy formation remains poorly understood. This study, therefore, aims to explore the influence of school committees on primary school policy development in Malang City, Indonesia. This research employed qualitative methods to collect data from 22 informants representing management of school committees across 26 primary schools. Key elements of committee formation were examined, including committee composition, ownership of the school committee decree (SK), tenure, and operational background of the committee. The findings indicate that the schools have not fully met the key elements necessary for establishing effective committees, even though they are designated as trigger schools. Nevertheless, this did not diminish the commitment and motivation of the school committees to contribute to the development of the schools. The results suggest that, despite structural challenges, school committees play a significant role in shaping school policies. Furthermore, the study highlights the need for an institutional improvement program aimed at strengthening the understanding of school committees regarding their rights and obligations, which is essential for the success of the school development initiatives.